Shoe cover - Abd Rajak, Aina Farahin; Ismail, Nur Ain Nadia; Othman, Siti Amira (Penerbit UTHM, 2020)
Shoe covers are defined as protective coverings for shoes worn by people that are working in a sterile environment to minimize contamination. Shoe covers are one of the safety product where it comes with varies sizes, shapes as well as different materials according to the applications or industries. Choosing the right one depends on several factors, including the size and type of shoes they’ll be covering as well as any work rules and regulations that apply. Shoes are the efficient transporters of infectious agents, hence shoe covers are essential tools that must have in order to prevent any contamination. The environment of workplace should be considered before decide in which protective shoe covers to use. There are two types of shoe covers which it is categorized as disposable and reusable as shown in Figure 1. The difference as well as pros and cons between both types of shoe covers are shown in Table 1.